Formative evaluation: implementation and main challenges present on schools or higher education - Beriche Lezama, Marcela Emperatriz (2021)
The concept of Formative Evaluation (FE) refers to a theming of interest in current educational politics. Its revision is needed specifically, when applied to the Peruvian context, in the interest of searching answers to the ever growing education emergency caused by its current sanitary crisis. From this premise, a documental analysis that integrates the inquiry and the systematization of regulatory frameworks and its theoretical-scientific background is proposed. With this approach, it’s been concluded that some fundamental components of a FE can be identified as keeping awareness, taking of decisions, a constant improvement, reflexive revision, self-regulation and learning autonomy. Therefore, it’s established that, its implementation can very well be considered effective, if a balance of regulatory dispositions from early schooling to higher education is achieved. Thus, the role of teacher implies one mayor challenge: It is necessary to guarantee the specialization and the effective pedagogical performance of the educator through all levels of education.